Review of Research methods for complexity theory in applied linguistics; Authors: Phil Hiver, Ali H. Al-Hoorie; Publisher: Multilingual Matters, 2020; ISBN: 978-1-78892-573-0; Pages: 286 - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2020)
When I found out about the upcoming publication of a book devoted in its entirety to research methods that can be used to investigate issues in applied linguistics (AL) within the framework of complex dynamic systems theory (CDST), I immediately decided to include it in my reading list and, time permitting, review it for SSLLT. On the one hand, research into learning and teaching second and foreign languages is one of the most vibrant lines of inquiry in AL and therefore it is only fitting that the appearance of such a ground-breaking volume should be recognized by the journal. After all, it is an indisputable fact that CDST has made major inroads into the domain of second language acquisition (SLA) and it is beginning to change or, should I say, revolutionize the ways in which different aspects of SLA are examined. This is perhaps most evident in the case of studies of individual difference (ID) factors (e.g., Dörnyei, MacIntyre, & Henry, 2014; Hiver, 2017; Oxford, 2017) and has also found its reflection in the special issue of SSLLT (1/2020), titled Investigating the Dynamic Nature of Individual Differences in L2 Learning, guest-edited by Laura Gurzynski-Weiss. In addition, one cannot help but notice that this theoretical stance has started to be seen as a new creed for many specialists, to the point that there is perhaps a danger of its being perceived as the only “correct” approach to shedding light on various facets of SLA. As Diane Larsen-Freeman writes in her excellent foreword to the book, “this new way of thinking has called into question the conventional ideas about language and its learning/development” (p. vii). On the other hand, I cannot call myself an ardent enthusiast of CDST, not because I cannot see its many merits or do not acknowledge its enormous potential for expanding our understanding of how languages are learnt or taught, but because I believe that only a diversity of approaches can help us better grasp the intricacies of these processes. Still, I was certainly thrilled to finally see a publication that, instead of merely trying to convince us that SLA research should be grounded in CDST, in fact makes an earnest attempt to illustrate how this can be done in practice.